Reinvigorating Growth in Resource-Rich Sub-Saharan Africa - Izvorski, Ivailo (World Bank, Washington, DC, 2018)
The strong economic performance of Sub-Saharan Africa’s resource-rich countries since the start of the 21st century has been celebrated as a return to more buoyant growth and renewed convergence with the advanced economies.Despite the recent progress in improving living standards and reducing poverty, achieving high and sustainable growth continues to be the main challenge for policymakers.Rwanda and Ethiopia have led Sub-Saharan Africa (SSA) in terms of per-capita growth since 2000, growing faster than South Asia. However, the gap between the resource-rich countries of Africa with East Asia and the Pacific (EAP), SAR, and the advanced economies has widened since 2010, underlining the difficulty of accelerating growth.Africa has often been portrayed as a continent of boundless natural riches that have helped pull the whole subcontinent forward. Indeed, resource-rich Africa accounts for a dominant part of SSA’s economy. Resource-rich SSA accounts for 70 percent of both the subcontinent’s GDP and physical capital, 60 percent of its natural capital, and nearly 40 percent of its population. For the continent in aggregate and in per capita terms, however, natural resources are just a bit higher than in the South Asia Region (SAR) and lag all other developing regions.One way of thinking of strengthening economic growth depends on more exploration and development of natural resources that should help increase the continent’s natural wealth, as has happened in many other developing regions.More importantly, durable prosperity in resource-rich Africa depends on building up the assets, or components of overall wealth, that are in relatively short supply. In recent years, the literature has started to focus on assets and assets diversification as a path to development, and the World Bank has led in this area. In this report, we emphasize the two complementary types of assets that Africa’s resource-rich countries need to build up to accelerate growth: one is within national borders and the other across borders.